Physiological demands of a simulated BMX competition - Louis, J.; Billaut, F.; Bernad, T.; Vettoretti, F.; Hausswirth, C.; Brisswalter, J. (International Journal of Sports Medicine, 2013)
The aim of this study was to investigate the physiological demands of Supercross BMX in elite athletes. Firstly athletes underwent an incremental cycling test to determine maximal oxygen uptake (VO2max) and power at ventilatory thresholds. In a second phase, athletes performed alone a simulated competition, consisting of 6 cycling races separated by 30 min of passive recovery on an actual BMX track. Oxygen uptake, blood lactate, anion gap and base excess (BE) were measured. Results indicated that a simulated BMX performed by elite athletes induces a high solicitation of both aerobic (mean peak VO2 (VO2peak): 94.3±1.2% VO2max) and anaerobic glycolysis (mean blood lactate: 14.5±4. 5 mmol.L - 1) during every race. Furthermore, the repetition of the 6 cycling races separated by 30 min of recovery led to a significant impairment of the acid-base balance from the third to the sixth race (mean decrease in BE: - 18.8±7.5%, p<0.05). A significant relationship was found between the decrease in BE and VO2peak (r= - 0.73, p<0.05), indicating that VO2peak could explain for 54% of the variation in BMX performance. These results suggest that both oxygen-dependent and -independent fuel substrate pathways are important determinants of BMX performance.